Unexpected Side Products in the Large-Scale Preparation of 2,3-Dihydro-1,1,2,2,3,3-hexamethyl-1H-indene - Raev, Vitaly; de Meijere, Armin; Hopf, Henning; Jones, Peter G. (Synlett, 2025)
During the development of an optimized procedure for the synthesis of 2,3-dihydro-1,1,2,2,3,3-hexamethyl-1H-indene significant amounts of 5-tert-butyl-2,3-dihydro-1,1,2,2,3,3-hexamethyl-1H-indene were formed, along with 5-tert-hexyl-2,3-dihydro-1,1,2,2,3,3-hexamethyl-1H-indene under certain conditions. The structures of 5-tert-hexyl-2,3-dihydro-1,1,2,2,3,3-hexamethyl-1H-indene and 5-tert-butyl-2,3-dihydro-1,1,2,2,3,3-hexamethyl-1H-indene were established by spectroscopic means and confirmed by X-ray single-crystal structure determinations. The mechanism for the formation of 5-tert-butyl-2,3-dihydro-1,1,2,2,3,3-hexamethyl-1H-indene is discussed.
Keywords: electrophilic aromatic substitution; highly crowded indenes; mechanisms; carbocation rearrangements; X-ray structural analysis